Daya Terima Dan Kandungan Serat Pangan Snack Bar “SANGTUL” Sebagai Pangan Fungsional Sumber Prebiotik - Sunarto Sunarto; Hendrayati Hendrayati; Nur Fajriany Anwar (Direktorat Politeknik Kesehatan Makassar, 2023)
Dietary fiber has the benefit of being a good source of prebiotics to maintain the health of the digestive tract. Kepok bananas contain inulin and fructooligosaccharides which are considered food for the intestinal microflora. Rice bran contains insoluble food fiber which can work as a source of prebiotics. This study aims to determine the acceptability and fiber content of the